2023
DOI: 10.1177/0887302x231160428
|View full text |Cite
|
Sign up to set email alerts
|

A Missing Site of Black Beauty History: The Black Beauty Supply Store

Abstract: With(in) retail spaces, Black Americans operate in a space with historical ties to inequality, dehumanization, and exclusion. This qualitative study situates the Black beauty supply store within these political and culturally relevant histories. Millennial perceptions of beauty, relationship to their hair, and the history of Black beauty supply stores are briefly covered in the literature review. Black feminist thought and Black feminist geographies informed the data analysis of interview transcripts from 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Even in virtual environments where Black women would be considered the majority participants, such as the natural hair vlogging industry, they still experience discrimination and bias specific to their identity (Hilton, 2020). The same sentiment is also found in beauty retail spaces, where millennial Black women revealed that they experience similar discrimination and a lack of representation in places where they buy beauty products (Reed, 2021).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Even in virtual environments where Black women would be considered the majority participants, such as the natural hair vlogging industry, they still experience discrimination and bias specific to their identity (Hilton, 2020). The same sentiment is also found in beauty retail spaces, where millennial Black women revealed that they experience similar discrimination and a lack of representation in places where they buy beauty products (Reed, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…Earlier studies conducted before 2011 (Makkar & Strube, 1995; Robinson-Moore, 2005, 2008; Lipford Sanders, 1996; Tucker, 2000; White, 2005) focused on understanding and comparing Black women’s beauty to Eurocentric standards. Studies published later, in 2021, move beyond comparison and instead focus on Black women’s perception of their beauty in relation to social media usage (Chambers, 2021), sexual well-being (Avery et al, 2021), and beauty retailing (Reed, 2021). In one instance, gendered and racial events were categorized to develop a taxonomy of microaggressions experienced by Black adolescent girls.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size and industry variance are similar to industry personnel in previous studies. 60,61 Of the responding participants, job experience ranged from 2 years to more than 10 years, with an even distribution of participants across the number of years. Job titles, supplied by the participants, were variations of product development positions and included the more product-oriented positions of Senior Designer, Technical Designer and Product Developer, as well as inclusion of employees in areas of product marketing, business process analyst and customer-contact manager.…”
Section: Participantsmentioning
confidence: 99%